Innovation in European telecommunication regulation: The diffusion of regulatory remedies - Gordon Klein; Julia Wendel (International Telecommunications Society (ITS), 2014)
Regulation of traditional narrow- and broadband networks remains a key issue in telecommunication policies. Due to the vertical structure of telecommunication markets and to promote investment, regulatory policies in many European Member States focus on wholesale obligations (so-called remedies) which mandate incumbent operators to share sell or split their infrastructure. On the European level, such remedies were introduced with regularity (e.g. 'Local Loop Unbundling' in 2000). Interestingly, in most cases the obligations were before implemented and tested at the national level. This paper analyses the process of diffusion of different regulatory means across European Member States and presents respective factors of influence on the event of (non-)adoption by the NRAs. Using a panel of European countries for a time period of 17 years, we find different patterns for different regulatory policies and in particular an effect of current state of broadband penetration levels.
Keywords: 330